1983
DOI: 10.1136/bmj.286.6380.1777
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognosis of women with breast cancer in New Zealand: study of survival to 30 years.

Abstract: The long term prognosis of women with breast cancer was studied by analysing retrospectively the 30 year survival of 2019 women with histologically proved breast cancer recorded at the National Cancer Registry in New Zealand between 1950 and 1954. Excess mortality rates for successive five year survival cohorts were calculated from the survival data. From the total cohort the excess mortality rate fell rapidly during the first 10 years and then became low after 20 years. There were no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…No definite conclusions can be drawn from our results, since the follow-up was far shorter than the 20 years considered by Hibberd et al (1983) Secondly, no differences were evident among disease-free probabilities of the three N groups of slow-growing tumours. Without emphasizing this result, the course of slow-growing tumours does not seem to be strictly dependent on lymph node involvement in a short follow-up.…”
Section: Discussioncontrasting
confidence: 42%
“…No definite conclusions can be drawn from our results, since the follow-up was far shorter than the 20 years considered by Hibberd et al (1983) Secondly, no differences were evident among disease-free probabilities of the three N groups of slow-growing tumours. Without emphasizing this result, the course of slow-growing tumours does not seem to be strictly dependent on lymph node involvement in a short follow-up.…”
Section: Discussioncontrasting
confidence: 42%
“…In the studies on patients treated before our series, the relative risks were higher than those evidenced in our cohort and late mortality remained higher than that of the general population after a follow-up of at least 20 years (Table VII) [12,13]. In the studies on patients treated virtually during the same period as our series, late mortality attained that of the general population within 10Á20 years of follow-up [14,16]. However, other studies showed that late mortality remained higher than unity with follow-up not exceeding 20 years [17,28].…”
Section: Other Long-term Studiesmentioning
confidence: 65%
“…Studies in the UK, Sweden, New Zealand, and The Netherlands found that about 20 years after diagnosis the life expectancy of patients with breast cancer resembles that of the general population (Brinkley and Haybittle, 1975;Hibberd et al, 1983;Rutqvist and Wallgren, 1985;Fentiman et al, 1994;Nab et al, 1994b), suggesting that patients can then be considered cured. However, breast cancer recurrences or metastases may develop decades after initial diagnosis and treatment (Hibberd et al, 1983;Nab et al, 1994b) and a higher death rate due to breast cancer has been reported up to 40 years after diagnosis (Rutqvist and Wallgren, 1985).…”
mentioning
confidence: 99%